(untitled) (Journal of Engineering, 2012)
lar water heating systems with heat pipes of three diameter groups of 16, 22 and 28.5 mm. The first and third groups had evaporator lengths of 1150, 1300 and 1550 mm. The second group had an additional length of 1800 mm. all heat pipes were of fixed condenser length of 200 mm. Ethanol at 50% fill charge ratio of the evaporator volume was used as the heat pipes working fluid. Each heat pipe condenser section was inserted in a storage tank and the evaporator section inserted into an evacuated glass tube of the Owens- Illinois type. The combined heat pipe and evacuated glass tube form an active solar collector of a unique design. The resulting ten solar water heating systems were tested outdoors under the meteorological conditions of Baghdad, Iraq. Experiments were carried out with no load, intermittent and continuous load conditions. Some tests, at no load, were carried out with and without reflectors. The overall system efficiency was found to improve with load conditions by a maximum of 55%. The system employing an 1800 mm evaporator length and 22 mm heat pipe (HP7) showed the best performance by higher water temperatures, overall useful energy gain and efficiency at various load conditions. System performance was predicted theoretically using electrical analogy derived from an energy balance. An agreement of within 14% was obtained between theoretical and experimental values.